Villar Palasí: about technocracy and school management - González Bertolín, Aurelio; Sanz Ponce, José Roberto (Historia y Memoria de la Educación, 2021)
University Professor José Luis Villar Palasí took charge of the Ministry of Science and Education in April 1968, after being nominated by the technocratic sector of the Government, with the political mission and personal conviction of reshaping the organisational structures of education in an attempt to stem the increasing unrest at universities. Nonetheless, he soon came to learn that the Spanish educational system as it stood required a complete renovation if it was to join the ranks of other advanced educational systems in the last quarter of the 20th century. In order to complete this task he recruited a team of qualified technocrats, most of them having independent political views and associations with international agencies and institutions. This ministerial team carried out a diagnosis of the imbalances and contradiction of the educational system at the time and then put forward a proposal for an educational reform, laid out in the so called Libro blanco (White Book). This document would become the foundational plan for the new General Education Act of 1970. However, regarding the matter of academic management, the wording of the Law deviated from the proposals made in Libro blanco, suppressing the Board of Directors. This work reflects on the ideological and political circumstances of the educational reform and Minister Villar Palasí himself. We also attempt to provide some clues as to the causes that led to the abolition of the Corps of Directors.